2011
DOI: 10.1073/pnas.1103630108
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies interactions that result inBacillus subtilisforming biofilms are mediated mainly by members of its own genus

Abstract: Many different systems of bacterial interactions have been described. However, relatively few studies have explored how interactions between different microorganisms might influence bacterial development. To explore such interspecies interactions, we focused on Bacillus subtilis, which characteristically develops into matrix-producing cannibals before entering sporulation. We investigated whether organisms from the natural environment of B. subtilis-the soil-were able to alter the development of B. subtilis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 57 publications
(69 reference statements)
0
97
1
Order By: Relevance
“…At the cellular level, differential responses to these local environments [e.g., as gradients of gene expression (36) or position-dependent cell specialization (37)] may increase phenotypic variability and promote bacterial adaptation during infection (38). The gradients formed inside packed colonies may also be used by bacteria as a cue for positioning during biofilm development (39). In the case of P. aeruginosa, Pvd has been identified as a virulence factor in the development of infectious biofilms (28,(40)(41)(42) and confocal imaging has revealed that the Pvd pathway is not activated uniformly within biofilms (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, differential responses to these local environments [e.g., as gradients of gene expression (36) or position-dependent cell specialization (37)] may increase phenotypic variability and promote bacterial adaptation during infection (38). The gradients formed inside packed colonies may also be used by bacteria as a cue for positioning during biofilm development (39). In the case of P. aeruginosa, Pvd has been identified as a virulence factor in the development of infectious biofilms (28,(40)(41)(42) and confocal imaging has revealed that the Pvd pathway is not activated uniformly within biofilms (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In both B. subtilis and P. aeruginosa, the regulatory pathways of antimicrobial production are closely entangled with those of biofilm formation, because matrix and antimicrobial genes are coexpressed (252)(253)(254)(255)(256)(257)(258). In the case of B. subtilis, matrix production can be triggered by antimicrobials produced by competitors (104,106,107,137). In other words, B. subtilis cells likely cooperate to compete against other soildwelling organisms.…”
Section: Life Cycle Biology: the Ecology Of Cell Differentiationmentioning
confidence: 99%
“…These kinases sense a variety of environmental signals, including self-generated products like surfactin and matrix (105,(135)(136)(137)(138). Once phosphorylated, Spo0A∼P indirectly represses the expression of sinR (139)(140)(141).…”
Section: Regulation Of Differentiation In B Subtilismentioning
confidence: 99%
“…2-200 μm in diameter (Fig. 4 A−D), that bear a striking resemblance to microbial microcolonies, i.e., micrometer-scale clusters of physically adjacent microbial cells (42). Some inclusions show negative crystal shapes evidencing entrapment during crystal growth (Fig.…”
Section: Microfossil Inclusionsmentioning
confidence: 99%